1998
DOI: 10.1038/sj.onc.1202501
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p16INK4a/p16α and p19ARF/p16β is frequently altered in non-small cell lung cancer and correlates with p53 overexpression

Abstract: The CDKN2 locus expresses two di erent mRNA transcripts, designated a and b. The protein product of the a transcript is the cell cycle inhibitor and tumour suppressor p16INK4a. The b transcript is translated in an alternate reading frame (ARF) and in humans encodes a 15 kDa protein (p19ARF). Immunohistochemical and Western analysis of p16INK4a has shown that the protein is downregulated in a signi®cant number of tumours, but less is known on the expression of the p19ARF. We have examined the expression of p16I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
82
3
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 28 publications
(47 reference statements)
10
82
3
1
Order By: Relevance
“…Although we optimized the assay for only one of the five antibodies tested, monoclonal 14PO2 from NeoMarkers, which has been used before in immunofluorescence assays (19), it is quite possible that comparable results may be obtained with other anti-p14 ARF antibodies. In agreement with earlier studies, the presence of immunoreactive p14 ARF was indicated by granular or diffuse nuclear staining, with or without nucleolar accentuation (17,18); cytoplasmic staining was observed even in cells with homozygous deletions of the INK4a gene and may thus be nonspecific. In some normal cells, cell lines and tumors, the staining pattern was predominantly nucleolar, consistent with the recently described nucleolar sequestration of MDM2 by p14 ARF (7,19,20).…”
Section: Correlation Between Arf Status and P14 Arf Expressionsupporting
confidence: 91%
See 3 more Smart Citations
“…Although we optimized the assay for only one of the five antibodies tested, monoclonal 14PO2 from NeoMarkers, which has been used before in immunofluorescence assays (19), it is quite possible that comparable results may be obtained with other anti-p14 ARF antibodies. In agreement with earlier studies, the presence of immunoreactive p14 ARF was indicated by granular or diffuse nuclear staining, with or without nucleolar accentuation (17,18); cytoplasmic staining was observed even in cells with homozygous deletions of the INK4a gene and may thus be nonspecific. In some normal cells, cell lines and tumors, the staining pattern was predominantly nucleolar, consistent with the recently described nucleolar sequestration of MDM2 by p14 ARF (7,19,20).…”
Section: Correlation Between Arf Status and P14 Arf Expressionsupporting
confidence: 91%
“…All four studies agree that p14 ARF loss is less common than down-regulation of p16 INK4a . Five of our lung cancers were negative for p16 INK4a but positive for p14 ARF , and this phenotype was observed in two earlier studies (17,18 (13). Interestingly, nine of 30 pancreatic carcinomas were positive for p14 ARF , suggesting that inactivation of this protein in this tumor type may not be as critical as abrogation of p16 INK4a .…”
Section: Correlation Between Arf Status and P14 Arf Expressionsupporting
confidence: 84%
See 2 more Smart Citations
“…4 The tumour suppressor gene p16 (p16 INK4a /CDKN2A) is a cell cycle regulator that is frequently inactivated in many different types of malignancies, including lung cancer. [5][6][7] It has been demonstrated that p16 gene may be transcriptionally inactivated by aberrant promoter methylation during tumorigenesis. 8 -10 The gene product, p16 protein, is a molecular component of the retinoblastoma protein (pRB) regulatory pathway, functioning as a specific inhibitor of cyclin-dependant kinases 4 and 6.…”
mentioning
confidence: 99%